Investigating the Parental and Media Influence on Gender Stereotypes and Young Student’s Career Choices in Pakistan - Hassan, Mehdi; Luo, Yingzi; Gu, Jianxiu; Mushtaque, Iqra; Rizwan, Muhammad (Frontiers in Psychology, 2022)
The study aimed to examine the impact of parental influence and media richness on gender stereotypes and career decisions among students at the secondary level in Pakistan. The sample size was 200 students, selected through a simple random sampling technique from government and private schools. Four questionnaires were used to gather data. The data was analyzed quantitatively using the Statistical Package for the Social Sciences (SPSS). Regression analyses were used to investigate the impact of parental influence (β=.50) on gender stereotypes and media richness influence (β= .26) on gender stereotype beliefs. Furthermore, parental, media, and gender stereotype behavior all have a significant impact on students' career choices (R2 =.694). On the scale of the parental influence and media richness, no significant gender differences were found. It is concluded that parental influence has a greater effect on students' gender stereotyping behavior and career choices.